Effects of inclusion of delay in the imposition of environmental tax on the emission of greenhouse gases. (August 2019) - Devi, Sapna; Gupta, Nivedita
Highlights: Imposition of environmental tax plays a vital role in dynamics of greenhouse gases. Corruption fades the effects of ecological taxation policy. Delay in the imposition of environmental tax may unstabilize the system. Stability of the system can be maintained by quantified applications of fair taxation policy. Abstract: In this research paper, we plan to study the relation among concentration of greenhouse gases, human population and environmental tax. For this purpose, a deterministic nonlinear mathematical model is proposed and analyzed in regard to the boundedness and persistence of its solutions, equilibria and their stabilities. Whenever, a policy is implemented, an automated delay comes into existence because outcomes of application of any policy always take some time to become visible. To see the effects of delay, analyses for the stability and direction of Hopf bifurcation for delay system are done. Critical value of the delay parameter is calculated theoretically and numerically, and then verified graphically. For verifications and descriptions of analytical findings, numerical simulations are performed. Graphical comparisons for different values of various parameters provides us some realistic and interesting results. Overall, model analysis shows that the increasing level of greenhouse gases can be controlled by applying environmental tax and imposing some restrictions on corruption.